Recombinant luteinizing hormone supplementation to recombinant follicle-stimulation hormone during induced ovarian stimulation in the GnRH-agonist protocol: A meta-analysis - Oliveira, Joao Batista A.; Mauri, Ana Lucia; Petersen, Claudia G.; Martins, Anice M. C.; Cornicelli, Joao; Cavanha, Mario; Pontes, Anaglória [UNESP]; Baruffi, Ricardo L. R.; Franco, Jose G. (Springer, 2007)
Purpose: to compare the efficacy of recombinant LH supplementation for controlled ovarian stimulation in recombinant FSH and GnRH-agonist protocol.Methods: Search strategies included on-line surveys of databases. The fixed effects model was used for odds ratio and effect size (weighted mean difference). Four trials fulfilled the inclusion criteria.Results: a fewer days of stimulation (p < 0.0001), a fewer total amount of r-FSH administered (p < 0.0001) and a higher serum estradiol levels on the day of hCG administration (p < 0.0001) were observed for the r-LH supplementation protocol. However, differences were not observed in number of oocyte retrieved, number of mature oocytes, clinical pregnancy per oocyte retrieval, implantation and miscarriage rates.Conclusions: more randomized controlled trials are necessary before evidence-based recommendations regarding exogenous LH supplementation in ovarian stimulation protocols with FSH and GnRH-agonist for assisted reproduction treatment can be provided.
Keywords: GnRH agonist; recombinant FSH; recombinant LH; ovarian stimulation